European Carbon Dioxide Removal Policy: Current Status and Future Opportunities - Tamme, Eve; Beck, Larissa Lee (Frontiers in Climate, 2021)
Over the past two years, the European Union, Norway, Iceland, and the UK have increased climate ambition and aggressively pushed forward an agenda to pursue climate neutrality or net-zero emissions by mid-century. This increased ambition, partly the result of the Intergovernmental Panel on Climate Change's landmark findings on limiting global warming to 1.5°C, has also led to a renewed approach to and revitalized debate about the role of carbon capture and storage and carbon dioxide removal. With increasing climate ambition, including a mid-century climate neutrality goal for the whole European Union, the potential role of technological carbon dioxide removal (CDR) is emerging as one of the critical points of debate among NGOs, policymakers, and the private sector. Policymakers are starting to discuss how to incentivize a CDR scale-up. What encompasses the current debate, and how does it relate to CDR technologies' expected role in reaching climate neutrality? This perspective will highlight that policy must fill two gaps: the accounting and the commercialization gap for the near-term development of a comprehensive CDR policy framework. It will shine a light on the current status of negative emission technologies and the role of carbon capture and storage in delivering negative emissions in Europe's decarbonized future. It will also analyze the role of carbon markets, including voluntary markets, as potential incentives while exploring policy pathways for a near-term scale-up.